Development economics and structuralist macroeconomics : essays in honor of Lance Taylor - Dutt, Amitava Krishna; Ros, Jaime (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2003)
Lance Taylor is considered to be one of the pre-eminent development economists in the world, and is known for his work on development planning, macroeconomics of development, stabilization policy and the global economy. The essays in this volume make contributions to each of these areas.
Includes bibliographical references and index.
oif 30/04/15
Loan
Keywords: Development economics; Finance -- Developing countries; Economic stabilization -- Developing countries; Globalization -- Economic aspects; Macroeconomics; Developing countries -- Economic policy